IMPACT OF PROCESS REENGINEERING ON TECHNICAL EFFICIENCY OF HEALTH CARE PROVIDERS - Blatnik, Patricia; Tajnikar, Maks; Tušak, Matej (Medicinski časopis, 2017)
Introduction: This article relates to the field of studying the impact of business process reengineering on technical efficiency. The reengineering method demonstrates its impact on selected business process, which is knee arthroscopy surgery. The impact of business process reengineering is studied on the example of a typical Slovenian general hospital. Methods: In the first step, we demonstrate the selected business process in the existing situation, while the second step demonstrates a business process, which could be reached in a potential situation. The demonstrated process is a basis for measuring the impact of business process reengineering on technical efficiency of a hospital. Results: The results obtained show that the business process reengineering increases the technical efficiency of the selected general hospital. The volume of labour input in the existing situation was higher by 67,88 %, and the value fixed assets after business process reengineering decreased by 36,25 %, and the value of material costs before business process reengineering increased by 50,9 %. Conclusion: The total volume of labour input in the potential situation thus decreased by 67,88 %, and the total volume of capital input decreased by 36,26 %. This means that business process reengineering does affect the hospital’s technical efficiency, since the latter would increase significantly if all the conditions of reengineering were met.